Study of the Correlation Between Vitamins and Iron on the Antioxidant Activity of Soy Milk Yogurt Enriched with Purslane (Portulaca oleracea L.) - Habibilah, Rodiah; Purwayantie, Sulvi (Media Publikasi Cendekia Indonesia, 2024)
Soy milk yogurt is a functional food that has health benefits. To improve the nutritional (vitamin) and functional (antioxidant) properties of yogurt, purslane leaves are added. This study aims to determine the relationship between vitamins C, E and iron on antioxidant activity (AA) in soy milk yogurt substituted with purslane. This research method uses random group 1 factor with a ratio of soy milk: purslane (100:0; 92.5:7.5; 85:15; 77.5:22.5; 70:30). Data were analyzed using correlation-regression. The results showed that the higher the purslane enrichment, the higher the vitamin E and vitamin C and each had a strong positive correlation with AA with an influence of 88.97% and 89.16% respectively. On the other hand, the higher the addition of purslane, the lower the iron content, causing AA to increase, with an Fe effect of 91.54% and a strong negative correlation. Thus, enriching yogurt with purslane leaves only increases vitamins C and E which have a positive impact on its antioxidant activity.